1989
DOI: 10.1139/x89-007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different inbreeding levels on filled seed production in Douglas-fir

Abstract: Matings of Douglas-fir (Pseudotsugamenziesii (Mirb.) Franco) were performed to develop inbreeding levels with inbreeding coefficient (F) values from 0.0 to 0.75. A strong inverse linear relationship was found between filled seed per cone and F at values ≤0.5. The following mean filled seed per cone values were obtained: outcross (F = 0.0), 31.6; half-sib cross (F = 0.125), 21.3; full-sib cross (F = 0.25), 16.7; parent–offspring backcross (F = 0.25), 15.5; self (F = 0.5), 1.2; second generation self (F = 0.75),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 0 publications
3
35
0
2
Order By: Relevance
“…They applied their model to six other similar published studies of pine and spruce species and found that synergism also provided a better fit to the data than did independent recessive lethals. A more recent study (Woods and Heaman, 1989) reported a linear decline in filled seed production with inbreeding coefficient in Douglas-fir. As with the study of Griffin and Lindgren (1985), the data were not analyzed on the In-scale.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They applied their model to six other similar published studies of pine and spruce species and found that synergism also provided a better fit to the data than did independent recessive lethals. A more recent study (Woods and Heaman, 1989) reported a linear decline in filled seed production with inbreeding coefficient in Douglas-fir. As with the study of Griffin and Lindgren (1985), the data were not analyzed on the In-scale.…”
Section: Discussionmentioning
confidence: 93%
“…As with the study of Griffin and Lindgren (1985), the data were not analyzed on the In-scale. Woods and Heaman present the mean filled seed production and percent yield at each level of inbreeding for each of the nine founder clones used in this study (table 2 of Woods and Heaman, 1989). If these means are In-transformed and the F = 0.75 class is excluded because data was available only for three clones, large and highly significant negative quadratic regression coefficients (P < 0.00 l) are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Selfing in most conifer species results in poor seed set (Woods and Heaman, 1989), decreased progeny size, reduced progeny vigor and increased susceptibility to pests (Orr-Ewing, 1954, 1965Sorensen, 1971). Under panmixia, a selfing rate of 2% is expected to occur in this seed orchard (49/49 2 ); however, an estimate of 15.2% was detected.…”
Section: Selfingmentioning
confidence: 99%
“…may be inevitable in advanced-generation seed orchards without operational modifications, such as sublining (Lowe and van Buijtenen 1986;McKeand and Bridgwater 1998). Negative effects of inbreeding have been observed at different life stages in many conifers, including Douglas fir, in terms of seed production (Griffin and Lindgren 1985;Sorensen and Cress 1994;Woods and Heaman 1989), nursery performance (Sniezko and Zobel 1988;Sorensen 1997;Woods et al 2002) and survival and growth vigor in early stages of field trials (Durel et al 1996;Orr-Ewing 1976;Sorensen and Miles 1982;Williams and Savolainen 1996). Therefore, decisions need to be made on tradeoffs between genetic gain obtained by selecting the best, but related, individuals and potential losses due to inbreeding between these individuals.…”
Section: Introductionmentioning
confidence: 99%